Use of a glycolipid inhibitor to ameliorate renal cancer in a mouse model. - Subroto Chatterjee (Public Library of Science (PLoS), 2013)
In a xenograft model wherein, live renal cancer cells were implanted under the kidney capsule in mice, revealed a 30-fold increase in tumor volume over a period of 26 days and this was accompanied with a 32-fold increase in the level of lactosylceramide (LacCer). Mice fed D- threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (D-PDMP), an inhibitor of glucosylceramide synthase and lactosylceramide synthase (LCS: β-1,4-GalT-V), showed marked reduction in tumor volume. This was accompanied by a decrease in the mass of lactosylceramide and an increase in glucosylceramide (GlcCer) level. Mechanistic studies revealed that D-PDMP inhibited cell proliferation and angiogenesis by inhibiting p44MAPK, p-AKT-1 pathway and mammalian target for rapamycin (mTOR). By linking glycosphingolipid synthesis with tumor growth, renal cancer progression and regression can be evaluated. Thus inhibiting glycosphingolipid synthesis can be a bonafide target to prevent the progression of other types of cancer.